Shake the Disease. Georges Marinesco, Paul Blocq and the Pathogenesis of Parkinsonism, 1893 - Hostiuc, Sorin; Drima, Eduard; Buda, Octavian (Frontiers in Neuroanatomy, 2016)
James Parkinson, in his ”Essay on the Shaking Palsy” from 1817 described for the first time the disease that later on carried his name. Its anatomical substrate remained controversial for over one hundred years. The first case that suggested the association between Parkinson’s disease and substantia nigra was published in 1903 by Blocq and Marinesco, two scientists who worked at Salpêtrière. The article described a 38 years-old man, with tuberculosis, who was admitted to the Charcot’s neurological ward because he also showed signs of unilateral Parkinsonism. During the autopsy, the investigators found a tubercle that destroyed the right substantia nigra. As the patient had overactive reflexes on the left side and the symptomatology matched exactly the localization of the tumor, Blocq and Marinesco suggested the Parkinsonism to be more likely a complication of tuberculosis and not an incidental finding. In this article, we will discuss the contribution of these two authors to the elucidation of the pathology of Parkinson’s disease, and highlight how even a single case report may play an essential role in the development of knowledge in biomedical sciences.